Novel lead-free NaNbO3-based relaxor antiferroelectric ceramics with ultrahigh energy storage density and high efficiency - Jie Jiang; Xiongjie Li; Ling Li; Shun Guo; Ji Zhang; Jing Wang; Heguo Zhu; Yiping Wang; Shan-Tao Zhang (Journal of Materiomics, 2022)
The development of environmentally friendly ceramics for electrostatic energy storage has drawn growing interest due to the wide application in high power and/or pulsed power electronic systems. However, it is difficult to simultaneously achieve ultrahigh recoverable energy storage density (Wrec > 8 J/cm3) and high efficiency (η > 80 %), which restricts their application in the miniaturized, light weight and easy integrated electronic devices. Herein, the novel NaNbO3-(Bi0.8Sr0.2)(Fe0.9Nb0.1)O3 relaxor antiferroelectric ceramics, which integrates the merits of antiferroelectrics and relaxors, are demonstrated to exhibit stabilized antiferroelectric phase and enhanced dielectric relaxor behavior. Of particular importance is that the 0.88NN-0.12BSFN ceramic achieves giant electric breakdown strength Eb = 98.3 kV/mm, ultrahigh Wrec = 16.5 J/cm3 and high η = 83.3 %, as well as excellent frequency, cycling and thermal reliability simultaneously. The comprehensive energy storage performance of NN-BSFN not only outperforms state-of-the-art dielectric ceramics by comparison, but also displays outstanding potential for next-generation energy storage capacitors.